The Cost-Volume Profit Analysis for Profit Planning at CV. Tabina Bersama - Aisyah, Mauliya (The Future of Education Journal, 2024)
This research is focused on analyzing cost-volume-profit (CVP) planning at CV. TABINA BERSAMA, a company that aims to optimize its financial decision-making and improve profitability. The study employs a qualitative research methodology, relying on secondary data sources, primarily the company’s financial reports, specifically the profit and loss statements from the years 2014 to 2023. These reports provide a comprehensive overview of the company's financial performance, allowing the researcher to explore trends in revenue, costs, and profit margins over a significant period. The results indicate a positive outlook for the company, with a projected 5% increase in profit from Rp. 58,150,000 in 2023 to Rp. 61,057,500 in 2024, signaling that CV. TABINA BERSAMA is positioned to continue operating profitably in the near future. The study emphasizes the importance of the contribution margin in profit planning, as it plays a critical role in determining the profitability of the company at different levels of production and sales. The contribution margin is an essential tool in CVP analysis because it allows the company to assess how changes in sales volume, fixed costs, and variable costs impact overall profitability. By utilizing this concept, the research underscores how businesses can make informed financial decisions, set appropriate sales targets, and optimize their cost structures to maximize profits. Furthermore, the research provides insights into how CV. TABINA BERSAMA can strategically use this information to maintain financial stability and support long-term growth. In essence, the study highlights the significance of CVP planning in navigating financial challenges, improving cost efficiency, and ensuring sustained profitability.